2020
DOI: 10.32598/jhnm.30.2.61
|View full text |Cite
|
Sign up to set email alerts
|

Clients' perception toward quality of postnatal care in the Gaza Strip, Palestine: A direction for health policy change"

Abstract: Most maternal and neonatal deaths occur during the postnatal period. Therefore, the quality of care provided by healthcare professionals at this critical time is crucial in reducing complications, morbidity, and mortality rates. Objective: The present study aimed to determine the perceptions of Palestinian women living in the Gaza Strip considering the quality of care they received in the early postpartum period. Materials and Methods: An analytical cross-sectional study was conducted using a selfadministered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The findings were in line with the results of Alkasseh A et al (2018) [10] which showed that among 200 postpartum mothers in Palestine rated the postnatal care they received as high. The overall Mean±SD scores for all domains of the scale were 3.93±0.66, from a maximum possible score of 5, which is above the neutral point of 3 However this result disapproved the findings of the previous study conducted in Sri Lanka by Wickramasinghe S et al (2019) [11] among 1300 postnatal mothers, reported that 49.9% had low perceived quality score and 50.03% rated as high perceived quality.…”
Section: Discussionsupporting
confidence: 91%
“…The findings were in line with the results of Alkasseh A et al (2018) [10] which showed that among 200 postpartum mothers in Palestine rated the postnatal care they received as high. The overall Mean±SD scores for all domains of the scale were 3.93±0.66, from a maximum possible score of 5, which is above the neutral point of 3 However this result disapproved the findings of the previous study conducted in Sri Lanka by Wickramasinghe S et al (2019) [11] among 1300 postnatal mothers, reported that 49.9% had low perceived quality score and 50.03% rated as high perceived quality.…”
Section: Discussionsupporting
confidence: 91%
“…The highest number of studies was found for measures regarding the experience of maternal care. Experience of maternal care measures often focused on specific concepts such as satisfaction (48,50,59,63,64,76,83,90) or respectful care (14,22,38,88,91,92) in a clinical setting. Studies including experience of care measures related to newborn care included satisfaction with (information related to) newborn care (50,57,60,88,93) or if contact with the newborn was facilitated(92).…”
Section: Resultsmentioning
confidence: 99%
“…Methods used in the different studies to validate indicators or measures varied (see Figure 3). Of the 24 studies reporting validation, seven used Cronbach alpha to assess for reliability (38,57,60,64,9395), eight studies used area under the receiver operating characteristic curve (AUC) (44,45,49,52,53,55,85,90) and two studies used confirmatory factor analysis (CFA)(50,93). One study used the Delphi method, and one used an external criterion(96).…”
Section: Resultsmentioning
confidence: 99%
“…. Of the 24 studies reporting validation, seven used Cronbach alpha to assess for reliability [41,60,63,67,[96][97][98], eight studies used area under the receiver operating characteristic curve (AUC) [47,48,52,55,56,58,88,93] and two studies used confirmatory factor analysis (CFA) [53,96]. One study used the Delphi method, and one used an external criterion [99].…”
Section: Plos Global Public Health (Fig 3)mentioning
confidence: 99%